THE BUILT HERITAGE OF THE FORMER CROWN DOMAIN OF MALINI. CAPITALIZATION OF HISTORICAL VESTIGES - COCIERU, Bogdan Ilie (Revista de turism - studii și cercetări în turism, 2021)
The Suceava County Crown Domain of Malini was the largest of the twelve rural estates that formed the Crown Domain. The most beautiful mountain road in the Kingdom of Romania crossed it. There were already two model peasant houses in the center of Malini in the first decade of the twentieth century. Each of the schools of the Crown Domain of Malini was equipped with a stage for public theatrical performances. The rich forest resources and the proximity to the Bukovina border have facilitated important transformations for the region of Malini, in particular in terms of the development of the village of Gainesti. The heritage of the Eastern Carpathians bearing the imprint of the Royal House could be the catalyst for a new tourist destination symbolically called the “Royal Heritage of the Eastern Carpathians”.